The early educational environment at five years of age in a European cohort of children born very preterm: challenges and opportunities for research - Alyssa Smith-Longee; Samantha Johnson; Adrien M. Aubert; Anna-Veera Seppänen; Veronique Pierrat; Michael Zemlin; Jo Lebeer; Iemke Sarrechia; Veronica Siljehav; Jennifer Zeitlin; Mariane Sentenac; On behalf of the SHIPS research group (BMC, 2024)
Abstract Background Early childhood education offers opportunities for stimulation in multiple developmental domains and its positive impact on long-term outcomes and wellbeing for children is well documented. Few studies have explored early education in children born very preterm (VPT; <32 weeks of gestation) who are at higher risk of neurodevelopmental disorders and poor educational outcomes than their term-born peers. The purpose of the study is to describe and compare the educational environment of children born VPT in European countries at 5 years of age according to the degree of perinatal risk. Methods Data originated from the population-based Screening to Improve Health In very Preterm infants (SHIPS) cohort of children born VPT in 2011/2012 in 19 regions from 11 European countries. Perinatal data were collected from medical records and the 5-year follow-up was conducted using parental questionnaires. Outcomes at 5 years were participation in early education (any, type, intensity of participation) and receipt of special educational support, which were harmonized across countries. Results Out of 6,759 eligible children, 3,687 (54.6%) were followed up at 5 years (mean gestational age 29.3 weeks). At 5 years, almost all children (98.6%) were in an educational program, but type (preschool/primary), attendance (full-time/part-time) and use and type of school support/services differed by country. In some countries, children with high perinatal risk were more likely to be in full-time education than those with low risk (e.g. Estonia: 97.9% vs. 87.1%), while the inverse pattern was observed elsewhere (e.g. Poland: 78.5% vs. 92.8%). Overall, 22.8% of children received special educational support (country range: 12.4-34.4%) with more support received by children with higher perinatal risk. Large variations between countries remained after adjustment for socio-demographic characteristics. Conclusions There are marked variations in approaches to early education for children born VPT in Europe, raising opportunities to explore its impact on their neurodevelopment and well-being.